2016
DOI: 10.1128/jcm.02803-15
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma Release Assays for Latent Tuberculosis: What Are the Sources of Variability?

Abstract: Interferon gamma release assays (IGRAs) are blood-based tests intended for diagnosis of latent tuberculosis infection (LTBI).IGRAs offer logistical advantages and are supposed to offer improved specificity over the tuberculin skin test (TST). However, recent serial testing studies of low-risk individuals have revealed higher false conversion rates with IGRAs than with TST. Reproducibility studies have identified various sources of variability that contribute to nonreproducible results. Sources of variability c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 32 publications
4
55
0
Order By: Relevance
“…We also observed a high degree of correlation between quantitative QFT-Plus (TB1 and TB2) and QFT results. For the small number of patients with discordant results, the discordance was mostly due to quantitative results bordering the assay cutoff (0.2 to 0.7 IU/ml) (19)(20)(21)(22). The latter finding is consistent with patterns of discordant results reported in prior IGRA reproducibility studies and suggests that sources of variability previously described for QFT also are acting on QFT-Plus (22).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We also observed a high degree of correlation between quantitative QFT-Plus (TB1 and TB2) and QFT results. For the small number of patients with discordant results, the discordance was mostly due to quantitative results bordering the assay cutoff (0.2 to 0.7 IU/ml) (19)(20)(21)(22). The latter finding is consistent with patterns of discordant results reported in prior IGRA reproducibility studies and suggests that sources of variability previously described for QFT also are acting on QFT-Plus (22).…”
Section: Discussionsupporting
confidence: 79%
“…For the small number of patients with discordant results, the discordance was mostly due to quantitative results bordering the assay cutoff (0.2 to 0.7 IU/ml) (19)(20)(21)(22). The latter finding is consistent with patterns of discordant results reported in prior IGRA reproducibility studies and suggests that sources of variability previously described for QFT also are acting on QFT-Plus (22). Importantly, in this study we found that 2.1% and 3.0% of 626 HCWs with no identifiable risk factors for LTBI had positive QFT and QFT-Plus results, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed by Banaei and colleagues, sources of variability can be broadly classified as preanalytical, analytical, postanalytical, manufacturing, and immunological (40). Figure 4 provides an overview of the major sources of variation with the QFT assay (15,40). Similar challenges also affect the reproducibility of the T-SPOT.TB assay.…”
Section: Igrasmentioning
confidence: 99%
“…Reproducibility studies have identified various sources of variability that contribute to nonreproducible results, and these studies have been systematically reviewed elsewhere (39). As reviewed by Banaei and colleagues, sources of variability can be broadly classified as preanalytical, analytical, postanalytical, manufacturing, and immunological (40). Figure 4 provides an overview of the major sources of variation with the QFT assay (15,40).…”
Section: Igrasmentioning
confidence: 99%
See 1 more Smart Citation